2022
DOI: 10.3390/molecules27031119
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Roxadustat on Erythropoietin Production in the Rat Body

Abstract: Anemia is a major complication of chronic renal failure. To treat this anemia, prolylhydroxylase domain enzyme (PHD) inhibitors as well as erythropoiesis-stimulating agents (ESAs) have been used. Although PHD inhibitors rapidly stimulate erythropoietin (Epo) production, the precise sites of Epo production following the administration of these drugs have not been identified. We developed a novel method for the detection of the Epo protein that employs deglycosylation-coupled Western blotting. With protein degly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“… 10 By exposing rats to 7% oxygen, Yukiko Yasuoka et al found that roxadustat produced EPO in some tissues stimulated by hypoxia, specifically regulating EPO production in the kidney. 11 Hypoxia stimulates various adaptive responses, many of which are mediated through transcriptional complexes of the HIF family, directly upregulating the transcription of genes involved in erythropoiesis, angiogenesis, vasomotor tone, metabolic pathways, and processes related to cell reproduction and survival. What is the mechanism by which roxadustat counteracts high-altitude hypoxia?…”
Section: Discussionmentioning
confidence: 99%
“… 10 By exposing rats to 7% oxygen, Yukiko Yasuoka et al found that roxadustat produced EPO in some tissues stimulated by hypoxia, specifically regulating EPO production in the kidney. 11 Hypoxia stimulates various adaptive responses, many of which are mediated through transcriptional complexes of the HIF family, directly upregulating the transcription of genes involved in erythropoiesis, angiogenesis, vasomotor tone, metabolic pathways, and processes related to cell reproduction and survival. What is the mechanism by which roxadustat counteracts high-altitude hypoxia?…”
Section: Discussionmentioning
confidence: 99%
“…This capillary Western blotting approach is also a useful method for the detection of Epo protein in both blood and urine. Instead of pre-purification, we introduced deglycosylation of the samples before Western blotting, as Desharnais P. et al did in combination with a capillary Western blotting [74,79,[86][87][88]. It is true that non-specific bands at around 25 and 50 kDa appear in our Western blotting, especially in blood, but those bands do not interfere with the appearance of glycosylated and deglycosylated Epo bands.…”
Section: Capillary Electromigration Methodsmentioning
confidence: 99%
“…Blood and/or urine samples are deglycosylated before our Western blotting [79,[86][87][88]]. An amount of 1 µL of 10% SDS is added to the 10 µL sample and boiled for 3 min at 100 Glycosylated and deglycosylated samples were applied to SDS-PAGE (10-20% gradient gel, 414893; Cosmo Bio, Tokyo, Japan).…”
Section: Methods Of Epo Detection By Deglycosylation-coupled Western ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Karin M. Kirschner et al reported that the HIF-PHD like roxadustat can combat hypoxic partial pressure in the treatment of preterm infant diseases(Kirschner, Kelterborn et al 2022), such as bronchial dysplasia. Yukiko Yasuoka et al found that roxadustat produced EPO in a number of tissues stimulated by hypoxia by exposing rats to 7% oxygen, speci cally regulating EPO production in the kidney(Yasuoka, Izumi et al 2022).…”
mentioning
confidence: 99%